Analisis Nilai Pendidikan Karakter dalam Novel Catatan Senja Karya Shakayla Adzkiya El Queena Sebagai Bahan Ajar Bahasa Indonesia di Sekolah Menengah Kejuruan - Prasetyawati, Afrilia Eka; Suharto, Teguh; Soleh, Dwi Rohman (Literasi : Jurnal Bahasa dan Sastra Indonesia serta Pembelajarannya, 2024)
Strengthening character education can be done through literature teaching in Indonesian language subjects. One of  the literature works is a novel. This research aimed at analyzing the values of character education in the novel Catatan Senja by Shakayla Adzkiya El Queena. This is a qualitative research. Data research were taken from dialogue among characters and situations in the novel which contain character education values. The research result showed fourteen character education values in the novel Catatan Senja. Included religious, honest, disciplined, hardworking, creative, independent, democratic, desire, respect for achievement, communicative, love of peace, like reading, social care, and be responsible. The values can be taught to students in vocational schools as learning material for strengthening character education as well as Indonesian language teaching materials, especially for grade XI and grade XII. It was based on learning outcomes in Merdeka curriculum that the students are able to evaluate ideas and views based on logical principles of thinking by reading various types of texts (nonfiction and fiction) from printing and electronic media.Keywords: Character, Education, Novel, Catatan Senja